Treatment of near-infrared photodynamic therapy using a liposomally formulated indocyanine green derivative for squamous cell carcinoma. - Tetsuro Maruyama; Yasunori Akutsu; Akiko Suganami; Yutaka Tamura; Hiromichi Fujito; Tomoki Ouchi; Naoki Akanuma; Yuka Isozaki; Nobuyoshi Takeshita; Isamu Hoshino; Masaya Uesato; Taro Toyota; et al. (PLoS ONE, 2015)
Photodynamic therapy (PDT) is a less invasive option for cancer treatment that has evolved through recent developments in nanotechnology. We have designed and synthesized a novel liposome system that includes an indocyanine green (ICG) derivative, ICG-C18, in its bilayer. In addition to its use as an optical imager to visualize blood, lymphatic, and bile flow, ICG has also been used as an optical sensitizer. In the present report, we evaluate the use of our novel liposome system, LP-ICG-C18, in PDT for squamous cell carcinoma in an autologous murine model.An excitation pulse beam (300 μJ/pulse) of a single band (800 nm) was used for sensitization. The cytotoxicity of the photodynamic therapy was evaluated in terms of cellular morphology changes, methyl thiazolyl tetrazolium (MTT) assay results, and terminal deoxynucleotidyl transferase-mediated deoxyuridine triphosphate-biotin nick end labeling (TUNEL) staining. We tested the enhanced permeability and retention effect of LP-ICG-C18 in tumor-bearing C3H/He mice using a near-infrared fluorescence imaging system and fluorescence microscopy. We also examined the antitumor effect of PDT by measuring tumor volume in tumor-bearing mice.Cell death and apoptosis were only observed in the PDT group receiving LP-ICG-C18. LP-ICG-C18 itself had no cytotoxic activity and showed good biocompatibility. LP-ICG-C18 accumulated on the tumor 24 hours after injection and was retained for approximately 3 weeks. Tumor cell apoptosis following PDT with LP-ICG-C18 was also observed under optical microscopy, MTT assay, and TUNEL staining.These findings suggest that LP-ICG-C18 may be an effective intervening material in PDT for malignant disease.